STEM-Based Learning Module Oriented Towards Balinese Ethnomathematics to Enhance Students' Creative Mathematical Thinking Abilities - Juliantara, Kadek Dwiki; Astawa, I Wayan Puja; Ardana, I Made (Universitas Pendidikan Ganesha, 2024)
Currently there is a challenge in learning mathematics, namely creative thinking. Many students were found to have low mathematical creative thinking abilities. Therefore, this study aims to develop STEM-based learning module with a focus on Balinese ethnomathematics to improve students' creative mathematical thinking. This research used a plomp research design, this research involved 105 high school students who continued through the preliminary research, prototyping and assessment stages. Various instruments are used, including validation sheets, practicality assessments, and essay tests, using descriptive analysis. This research resulted in the creation of quality STEM-based learning modules, validated for their effectiveness and practicality. This module integrates elements of Balinese ethnomathematics, featuring instructional videos and interactive GeoGebra elements. This study identified learning trajectories involving three main activities related to middle school geometric transformations. The implementation of the module provides a significant increase in students' mathematical creative thinking abilities, as evidenced by the post-test results and the calculated n-gain value. In conclusion, the module developed is a valid, practical and effective tool for improving students' creative mathematical thinking, which combines STEM principles and Balinese ethnomathematics. The study emphasizes the importance of integrating cultural elements into educational materials to foster a deeper understanding of mathematical concepts. These findings underscore the potential of this approach to make a positive contribution to mathematics education, particularly in the context of local cultural relevance.